Transfer Behaviour in Migrant Sending Communities - Tanika Chakraborty; Bakhrom Mirkasimov; Susan Steiner (Institute for the Study of Labor (IZA), 2013)
We study how international migration changes the private transfers made between households in the migrant sending communities of developing countries. A priori, it is indeterminate whether migration and remittances strengthen or weaken the degree of private transfers in these communities. From a policy perspective, public income redistribution programmes would have an important role to play if migration reduced the extent of private transfers. Using household survey data from Kyrgyzstan, we find that households with migrant members (as well as households receiving remittances) are more likely than households without migrants (without remittances) to provide monetary transfers to others, but less likely to receive monetary transfers from others. This suggests that migration is unlikely to lead to a weakening of private transfers.
Keywords: D63; F22; O12; I30; 330; private transfers; cash and labour exchange; migration; Kyrgyzstan; Central Asia